Understanding Why Insurance Companies Do Not Spin Off Sharia Business Units from the Corporate Entrepreneurship Angle Post the Issuance of the Financial Sector Development and Strengthening Law (PPSK Law) - Adriana, Dadi; Hartoyo, Hartoyo; Syarief, Rizal; Anggraeni, Elisa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Based on the results of situational analysis, problematic situations, strategies, and the proposed model as explained above, several conclusions can be drawn. The high number of Muslim people in Indonesia encourages companies to innovate in creating new products that are easier for the public to understand, especially related to Sharia insurance. The existing condition of the insurance industry is driven by the real growth trend of Sharia insurance customers, which can be used as a measure of industry growth. When compared with other countries, there are similarities and differences between Sharia and conventional insurance governance. This can be used as a comparative reference to optimize the management of the Sharia insurance industry. Based on the results of the situation analysis, it is known that the current condition of the Sharia insurance industry is not optimal because there has been no serious effort from the regulator to integrate all potential from upstream to downstream in all elements of the Sharia insurance industry. From the results of the interview analysis, it was revealed that the strategy considered to be the most effective and the main priority in developing the Sharia insurance industry is increasing human resource competency through intensive and continuous training. This aims to overcome the shortage of professional human resources in the fields of insurance and sharia economics while ensuring quality improvement.